Effect of fungicides and cultivar on cereals to Trichoderma afroharzianum ear infection in the field related to fungicide treatment and crop cultivar - Pfordt, Annette; Pruszynski-Beck, Susanne; von Tiedemann, Andreas (Frontiers in Agronomy, 2025)
Members of the genus Trichoderma are widely recognized as beneficial fungi and frequently applied as biocontrol agents. However, recent studies have identified Trichoderma afroharzianum as a pathogenic species, capable of infecting maize, wheat, and barley under greenhouse conditions. Its pathogenic potential in small-grain cereals under field conditions, however, has been so far unexplored. To evaluate its pathogenic potential, two-year field trials (2023 and 2024) were conducted using ten wheat, five barley, two rye, and one triticale cultivar. Artificial inoculation was carried out at full flowering using a spray inoculation with pathogenic T. afroharzianum isolates obtained from maize and water as control. Three fungicides were applied: untreated control, foliar treatment before inoculation, and ear application after inoculation. Disease development was assessed based on colonization rate of harvested kernels, and thousand kernel weight (TKW). The results showed significant differences in susceptibility between and within cereal species. T. afroharzianum was able to colonize wheat and barley ears under field conditions, with some cultivars showing significant reduction of 12 g in TKW and high colonization rate up to 48%. In contrast, rye and triticale exhibited much lower colonization rates of 0-10%. Fungicide treatments had varying levels of efficacy. Ear application after flowering was most effective in reducing colonization and preventing yield loss, whereas early foliar treatment showed limited effect. These findings indicate that T. afroharzianum may represent a relevant pathogen in cereal production adding a new ear disease in cereals and requiring monitoring and enhanced fungicide applications in the future, unless less susceptible cultivars are identified and utilized in practice.